Peradaban Terbentuknya Mushaf Al-Qur’an (Sejarah Terbentuknya Mushaf Rasm Ustmani) - Aldie Fitra; Lia Listiana (Qolamuna : Jurnal Studi Islam, 2022)
This study is entitled: Civilization of the Formation of the Al-Qur'an Mushaf (History of the Formation of the Ustmani Mushaf), the discussion is the history of the formation of the Ottoman rasam, while the purpose of this study is to find out how the struggles to be able to launch the Ottoman Mushaf after the Muslim debate occurred because of the different ways. the reading of the holy verses of the Qur'an in the hope of adding knowledge and insight to the reader, the methodology or approach used in library research, while data collection is carried out by analyzing data/exploring several journals/books and documents both in print or electronic form as well as other sources of data or information deemed relevant to the research or study. The discussion in this study is related to the bookkeeping of the Ottoman manuscripts which was motivated by differences of opinion in reading the Qur'an to Muslims, the policy of the Uthman caliph to record the manuscripts and become the Ottoman manuscripts, after finishing the opening of the Uthman caliph, he read the final manuscript in front of his friends, and burned other manuscripts, and caliph Umar sent copies of the Ottoman manuscripts to various Islamic regions and included them with their reciters. In writing, there are still differences of opinion among scholars' taufiqi or ijtihad scholars'. Keywords: Al-Qur'an Mushaf, Ottoman Mushaf, Civilization, History